Creando ambientes de aprendizaje a través de las lesson study: una experiencia en la formación inicial de docentes de educación infantil - Peña-Trapero, Noemí; Servan-Núñez, María José; Rodriguez-Robles, Cristina; Soto-Gómez, Encarnación (My University, 2017)
This paper will present the Lesson Study developed during the first year of the Infant Education Degree Course at Malaga University, as part of a coordinated project based on the subjects Didactics, Organisation, and Inclusive Education. Students designed and implemented actual learning environments for an Early Years (ages 3 to 6 years) using Lesson Study. Our aims were to use practical training as a way to generate reflection-from-action and to ensure our students developed the teaching skills necessary for schools in the 21st century. The task revolved around 4 core areas: • A selection of contents based on relevance, depth and interdisciplinarity. • A methodology based on activity, experimentation and research. • A teaching role based on designing and accompanying students through tutoring. • Assessment for learning through an electronic portfolio. The students were divided into eight small groups (of 4 or 5). We prepared a series of written guides which were used throughout the process, along with our presence in both the classroom and online during each of the phases. Our goal was for this group work to be the context –in the form of discussions and debates at the start, and design, experimentation and analysis at the end– for the different theory contents worked on at the same time in the subjects. It was a way to involve students holistically in the process and for them to experience and feel it through their emotions and their bodies, aspects which are traditionally overlooked in university training contexts. Living and building an educational experience requires an ongoing and cyclical transition from knowledge to practical thinking. The phases dedicated to searching for a focal point and a design gave students the opportunity to theorise on practice by reading, documenting themselves and researching ideas they could use to create within a living experience context. This process of reflection-on-action involves encouraging and stimulating the prospective teachers to identify, analyse and reformulate not only the proclaimed theories which adorn practice but also the theories-in-use which govern it. Furthermore, by developing and implementing the learning environments they had designed, the prospective teachers could experiment with the theory, leading to the construction of those teaching skills which are automatically activated when we face new actions and new contexts. One aspect we found striking when collecting evidence was how students overcame different cognitive conflicts during the process, and how they were able to directly experience the autonomy a teacher has to design learning contexts connected to childhood interests. Moreover, and more importantly, they saw first-hand how the Lesson Study process, with all its phases and cooperative work, allowed them to combine their creativity and singular talents in a common project. In this case, the Lesson Study process facilitated the construction of solid structures related to meaning, the educational process, and, above all, the need to recalibrate what it means to be an infant school teacher: a creative, relevant, complex experience that requires them to recreate the knowledge and experience which prospective infant school teachers bring to the university training process.
Creating learning environments through lesson study: an experience in initial training for early years teachers
Keywords: Profesores - Formación profesional - Congresos; Formación inicial de docentes; Educación infantil; Lesson study; Conocimiento práctico